Influence of authoritative parenting, reading attitude, and early literacy on reading comprehension - Siti Wan Aminah Wan Norudin; Norlizah Che Hassan; Marzni Mohamed Mokhtar; Maizura Yasin; Mohd Shahridwan Ramli (Intelektual Pustaka Media Utama, 2026)
This study examines the relationships between authoritative parenting or keibubapaan autoritatif (KA), parents’ reading attitudes or sikap membaca Ibu Bapa (SMIB), early literacy activities or aktiviti literasi awal (ALA), and students’ reading comprehension which measured by skor kefahaman membaca (SKORKM), focusing on the role of ALA as a mediator. Utilizing cross-sectional surveys in a quantitative approach, data were collected from 393 year-5 pupils and their parents across 15 primary schools in Kelantan, Malaysia. Participants were selected through a multilevel random sampling method. The research design incorporated both descriptive statistics and inferential analysis using structural equation modeling. The structural path analysis revealed that only ALA had a significant direct influence on SKORKM. Moreover, ALA fully mediated the relationships between KA and SKORKM, as well as between SMIB and children’s reading comprehension. These findings suggest that KA and positive parental reading attitudes impact SKORKM primarily through the practice of ALA at home. The study successfully developed a new structural equation model that elucidates how family contextual factors, including KA, SMIB, and ALA, are associated with SKORKM achievement.